2013
DOI: 10.1063/1.4829919
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of contact theories for the manipulation of biological micro/nanoparticles in the form of circular crowned rollers based on the atomic force microscope

Abstract: Articles you may be interested inDiagonal control design for atomic force microscope piezoelectric tube nanopositioners Rev. Sci. Instrum. 84, 023705 (2013); 10.1063/1.4790474Numerical simulations of electrostatic interactions between an atomic force microscopy tip and a dielectric sample in presence of buried nano-particles A control approach to cross-coupling compensation of piezotube scanners in tapping-mode atomic force microscope imaging Rev. Sci. Instrum. 80, 043709 (2009); This article has dealt with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…To compare the elastic properties' differences between cancer cells and their counterpart normal cells, the relative Young's modulus ( ) is defined as follows: R = cancer cell / counterpart normal cell (10) where cancer cell and counterpart normal cell are Young's moduli of the cancerous and normal cells, respectively. The results of this paper show that the relative Young's modulus is about 0.75 which shows the softness of cancer cell in comparison with a normal one.…”
Section: Comparison Between the Cancerous And Healthy Breast Cells' Rmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the elastic properties' differences between cancer cells and their counterpart normal cells, the relative Young's modulus ( ) is defined as follows: R = cancer cell / counterpart normal cell (10) where cancer cell and counterpart normal cell are Young's moduli of the cancerous and normal cells, respectively. The results of this paper show that the relative Young's modulus is about 0.75 which shows the softness of cancer cell in comparison with a normal one.…”
Section: Comparison Between the Cancerous And Healthy Breast Cells' Rmentioning
confidence: 99%
“…There are various devices hired to measure biological cell's different properties, one of which is atomic force microscopy (AFM) [16]. The advantage of AFM over other methods is its capability to present information about other properties such as adhesion distribution, friction, elasticity module, viscoelastic characteristics and surface topography [10]. AFM function in the case of soft surfaces, such as cells and polymers, has some complexities; Weisenhorn et al obtained force-distance and force-indentation depth curves for elastomers, rubbers and biological cells in contact moments and extracted the parabolic curves.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to simulate this biological cell at contact moment, a spherical bundle of DNA has been considered. Also, assuming DNA molecule to be cylindrical or circular capped cylinder, Korayem et al [16] compared the contact mechanics of these two geometries with the results obtained from the spherical geometry, and concluded that the indentation depth created in the spherical geometry is greater than that produced in the other two types of geometries.…”
Section: Elasto-plastic Impact Theory Of Andrewsmentioning
confidence: 99%
“…Korayem et al developed and modeled a number of contact theories for biological nanoparticles shaped as cylinders and circular crowned rollers for application in the manipulation of different biological micro/nanoparticles using AFM. They adapted the contact theory in accordance with the geometry of the particles to the extracted force-displacement curve via AFM and calculated the critical time and force in the manipulation using the indentation depth and contact radius [14].…”
Section: Introductionmentioning
confidence: 99%